Evaluating the transferability of empirical models of debris-covered glacier melt - A. Winter-Billington; R. D. Moore; R. Dadic (Journal of Glaciology, 2020)
Supraglacial debris is significant in many regions and complicates modeling of glacier melt, which is required for predicting glacier change and its influences on hydrology and sea-level rise. Temperature-index models are a popular alternative to energy-balance models when forcing data are limited, but their transferability among glaciers and inherent uncertainty have not been documented in application to debris-covered glaciers. Here, melt factors were compiled directly from published studies or computed from reported melt and MERRA-2 air temperature for 27 debris-covered glaciers around the world. Linear mixed-effects models were fit to predict melt factors from debris thickness and variables including debris lithology and MERRA-2 radiative exchange. The models were tested by leave-one-site-out cross-validation based on predicted melt rates. The best model included debris thickness (fixed effect) and glacier and year (random effects). Predictions were more accurate using MERRA-2 than on-site air temperature data, and pooling MERRA-2-derived and reported melt factors improved cross-validation accuracy more than including additional predictors such as shortwave or longwave radiation. At one glacier where monthly ablation was measured over 4 years, seasonal variation of melt factors suggested that heat storage significantly affected the relation between melt and energy exchange at the debris surface.